THE ESSENCE AND CONTENT OF THE MILITARY RITUAL - MILITARY ASSOCIATION IN SEPARATE CIS COUNTRIES - Shukhratjon Shakirov (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the essence and content of the military oath, certain aspects of the requirements and the procedure for conducting this military ritual, taking into account the history of its origin and subsequent development by influencing its content, forms and methods of organizing traditions, historical aspects and other factors of individual CIS countries. The role and importance of the military oath in the upbringing of a serviceman, improving his moral and combat qualities and the formation of a moral and ethical atmosphere and military comradeship in military collectives as a whole are also studied.